2011
DOI: 10.5194/cp-7-221-2011
|View full text |Cite
|
Sign up to set email alerts
|

North Atlantic abrupt climatic events of the last glacial period recorded in Ukrainian loess deposits

Abstract: Abstract. Loess deposits are widely distributed in the Northern Hemisphere, where they have recorded not only the glacial-interglacial cycles, but also millennial-timescale changes resembling those in marine and ice cores. Such abrupt variations are clearly marked in western European series, but have not yet been evidenced in the East of the continent. Here we present results of the high-resolution investigation of a Weichselian Upper Pleniglacial loess sequence (∼38-15 ka) from Stayky, Ukraine. The stratigrap… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
90
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 81 publications
(96 citation statements)
references
References 36 publications
3
90
0
Order By: Relevance
“…And the NGRIP δ 18 O and Ca 2 +  records and Qinghai Lake WI also show wetter and warmer climate from 30 ka to 11 ka, but the grain size of Ili loess shows an opposite trend. we find, on millennial timescales and long trend, the grain size of the Stayky loess from the eastern Europe29 is similar with that of XEBLK, showing H1 is colder than LGM, wetter and warmer climate from 30 to 16 ka and colder and dryer climate form 16 to 11 ka (Fig. S4).…”
Section: Discussionsupporting
confidence: 53%
“…And the NGRIP δ 18 O and Ca 2 +  records and Qinghai Lake WI also show wetter and warmer climate from 30 ka to 11 ka, but the grain size of Ili loess shows an opposite trend. we find, on millennial timescales and long trend, the grain size of the Stayky loess from the eastern Europe29 is similar with that of XEBLK, showing H1 is colder than LGM, wetter and warmer climate from 30 to 16 ka and colder and dryer climate form 16 to 11 ka (Fig. S4).…”
Section: Discussionsupporting
confidence: 53%
“…This scenario is in agreement with the enhancement in the frequency of storms from the N/NW, as suggested by Antoine et al (2009b) based on a sedimentological study, and corroborates the possible predominant dust deposition direction proposed by Marković et al (2008) for the Surduk area based on a loess thickness investigation. It also fits with the 850 hPa winds reconstructed by Rousseau et al (2011) and Sima et al (2013).…”
Section: Possible Climatic Pattern To Explain C 4 Episodesmentioning
confidence: 99%
“…Rapid environmental changes have also been identified in loess sequences further east (Haesaerts et al, 2003;Rousseau et al, 2001Rousseau et al, , 2007Rousseau et al, , 2011Gerasimenko and Rousseau, 2008;Antoine et al, 2009). They are expressed in the loesspaleosol stratigraphic succession, and in the variations of different indices: grain size index, magnetic properties, carbon isotope ratios, and, where available, in the pollen records.…”
mentioning
confidence: 99%
“…Following investigations by Kukla (1977), a link between Central and Eastern Europe was established on the basis of sequences from Dolní Věstonice, in the Czech Republic (e.g., Fuchs et al, 2012;Antoine et al, 2013), and Vyazivok, in the Ukraine (e.g., Rousseau et al, 2001). Recently, using high-resolution data from Nussloch, Germany, and another Ukrainian site, Stayky, Rousseau et al (2011) suggested that the North Atlantic climate signal has been recorded throughout the European loess band, at least as far as 30 • E.…”
mentioning
confidence: 99%